Religious extremism and the role of universities in confronting it - Al-Aani, Assistant Professor Dr. Khalil Ibrahim Saeed Al-Aani Saeed; Mohammed, Assistant Lecturer Iman Jassem Mohammed; Habitar, Assistant Lecturer Zainab Abdullah Habitar (Sulaimani Journal for Humanities, 2026)
This research aims to study the problem of (ideological extremism and the role of educational institutions in confronting it "universities as a model"), and the problem of extremism is a problem that is sweeping many Arab universities, as no Arab university today is immune from the possibility of falling prey to destructive extremist ideas and behaviors, and this problem has increased recently and has become a bitter reality that our society lives, and it has also become a threat to society as a whole by striking at its educational structure and infrastructure and destroying the minds of its children, which carries within it a negative content that is reflected in the culture of society. Its appearance was evident in imitating Western cultures, so it began to pretend to be organizations that are outside of society and reject its standards, to practice violence and self-destruction of students. The study reached the following results, the most important of which were: the role of universities in establishing the Islamic faith, spreading moderation and acceptance of others, and providing the opportunity to open the door to discussion and constructive dialogue among students. It also represented the role of universities in confronting extremism by directing scientific research to know the causes of extremism and confronting it. Therefore, the aim of the research revolves around ideological extremism, and then determining the role of educational institutions in confronting it, especially universities.
Keywords: extremism; ideological; role; educational institutions; universities